FORECASTING BUSINESS PROCESSES IN THE MANAGEMENT SYSTEM OF THE CORPORATION - Yaremko, Svitlana A.; Kuzmina, Elena M.; Savina, Nataliia B.; Yepifanova, Iryna Yu.; Gordiichuk, Halyna B.; Mussayeva, Dinara (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
One of the key issues in corporate management is business process management. That is why the greatest interest for company analysts is the issue of effective forecasting of business processes. In today’s digitalization of the economy, integration and automation of business processes have become the main priorities for achieving efficiency and effectiveness of companies, and especially for effective management decisions. This problem can be solved with the help of integrated systems, which are tools for effective management decisions, modeling and optimization of business processes. The article provides an analytical review of known forecasting methods and identifies the features of their application, analyzes the advantages and disadvantages that will take them into account in modeling the company and promote economic development, competitiveness and optimize business processes.